Development of a model clinical rotation in a non-traditional setting for interns in occupational therapy - Recto-Legaspi, Anna J.A. (2000)
Emerging trends in health service provision takes the Occupational Therapist outside the traditional practice areas (i.e. hospital settings). OTs now find themselves assuming diversified roles such as that of entrepreneur, administrators and consultant in addition to performing the responsibilities of OT practitioner. Training programs need to address such emerging trends to prepare future professionals for the demands of practice after graduation. The College of Allied Medical Professions, University of the Philippines Manila collaborated with the Able Center and Skill Builders Therapy Center in setting up an internship program to address this need. A one-month clinical internship program was established with the intent of exposing the interns to the required competencies of an entry-level OT entrepreneur, an administrator and consultant as well as to the OT practitioner in a non-traditional practice setting. At the end of its first year of implementation it was determined that a more structured program would enhance the intern's perceptions and acquisition of entry-level skills of OT entrepreneur, administrator and consultant. An instructional design was developed and this was reviewed for its content validity. Thirty three Occupational Therapists and twelve interns of Occupational Therapy participated in the study. There appeared to be a general acceptance for the content of the instructional design. Recommendations regarding selected learning activities, the time allotted for the completion of the activities and the evaluation methods chosen were incorporated into the revised instructional design. At the conclusion of the study the following recommendations were made: 1) a second round of review of the revised instructional design by the same respondents of the study; 2) an evaluation of the program as implemented for the OT interns of School Year 2000-2001; 3) closer coordination with CAMP to address student preparedness to participate in the prescribed learning activities. There was some skepticism noted when professionals reviewed the instructional design. Acceptance of such innovative programs should be addressed by careful study and deliberation by the profession. The changing healthcare environment will mean a change in employment opportunities for future OT professionals. It is the educator's responsibility to ensure that graduates are prepared to meet the demands of this changing environment.
Special project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Occupational therapy -- Study and teaching (Residency); Internship and Residency